1987
DOI: 10.1002/1097-0142(19870915)60:6<1306::aid-cncr2820600624>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

The presence of tumor cells in bone marrow at the time of first recurrence of breast cancer

Abstract: The occurrence of bone marrow carcinosis was investigated in 380 patients at the time of first recurrence of breast cancer. Results were related to results from radiographic bone survey, 99mTc MDP bone scintigraphy, clinical examination and serum alkaline phosphatase and serum calcium levels. Eighty-seven patients (23%) had tumor cells in the bone marrow. X-rays showed metastases in 78% of the patients with and in 16% of the patients without bone marrow carcinosis. The diagnostic efficiency of x-rays with bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
3

Year Published

1988
1988
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 15 publications
1
36
0
3
Order By: Relevance
“…The organisation and results of this study have been published previously (Kamby et al, 1987b obtain tissue for histological verification of metastasis (Kamby et al, 1987a).…”
Section: Methodsmentioning
confidence: 99%
“…The organisation and results of this study have been published previously (Kamby et al, 1987b obtain tissue for histological verification of metastasis (Kamby et al, 1987a).…”
Section: Methodsmentioning
confidence: 99%
“…Clinically, it is important to suspect DCBM when a patient with advanced breast cancer manifests a hematological disorder, such as anemia or thrombocytopenia. Diagnostic tools, such as 18 F-fluorodeoxyglucose positron emission tomography/computed tomography and blood smear examination have been proposed for the diagnosis of DCBM (18)(19)(20); however, examination of a BM biopsy and/or aspirate remains the gold standard (3,14). Pathologically, DCBM is characterized by the diffuse infiltrative growth of tumor cells in the BM, and normal components, apart from bone trabeculae, are largely replaced by the tumor infiltrate (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the association between isolated tumor cells in the BM and clinically symptomatic BM metastasis has not been fully elucidated (11,14), whereas clinically evident BM metastasis is relatively common and often progresses to DCBM in patients with metastatic or recurrent breast cancer. It was reported that BM metastases were identified in 6-79% of breast cancer patients at autopsy (15)(16)(17), and 27% of autopsy cases were clinically diagnosed with BM metastases prior to autopsy (15).…”
Section: Introductionmentioning
confidence: 99%
“…Tumour cells are found in bone marrow at the time of the recurrence of breast cancer [12] and are found in 23% of patients without detection of metastases by radiographs or bone scans [5]. Bone man'ow scans have been shown to prove bone invasion earlier that routine radiographs [3].…”
Section: Discussionmentioning
confidence: 99%